2023
DOI: 10.1159/000529141
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Benzodiazepines and Z-Drugs Use during Pregnancy and Adverse Birth and Neurodevelopmental Outcomes in Offspring: A Population-Based Cohort Study

Abstract: <b><i>Introduction:</i></b> The use of benzodiazepines and/or z-drugs in women of childbearing age has increased. <b><i>Objective:</i></b> The aim of the study was to evaluate whether gestational benzodiazepine and/or z-drug exposure is associated with adverse birth and neurodevelopmental outcomes. <b><i>Methods:</i></b> A population-based cohort including mother-child pairs from 2001 to 2018 in Hong Kong was analysed to compare gestationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 44 publications
0
25
0
Order By: Relevance
“…ADHD was defined by each site using specific diagnosis and medication codes as reported in previous studies and detailed in Supplementary Table 1 (refs. 30 , 31 ). In Hong Kong, New Zealand and Taiwan, children with either one ADHD diagnosis or one ADHD medication prescription were regarded as having the outcome.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ADHD was defined by each site using specific diagnosis and medication codes as reported in previous studies and detailed in Supplementary Table 1 (refs. 30 , 31 ). In Hong Kong, New Zealand and Taiwan, children with either one ADHD diagnosis or one ADHD medication prescription were regarded as having the outcome.…”
Section: Resultsmentioning
confidence: 99%
“…First, most data originated from reimbursement or other administrative purposes rather than research purposes, which represent a variety of data sources, healthcare settings, coding practices, diagnostics criteria, and treatment approaches. Nevertheless, data sources included in this study are all based on high-quality territory-wide electronic health records with robust mother–child linkage and comprehensive information on maternal and child medical records that have been used extensively for pregnancy-related studies 30 , 34 36 . Moreover, we applied data source-specific identification criteria for not only the exposure and outcome but also the covariates to maximize the comparability of variables included in the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31,32 The negative control design in our study, which redefined different risk periods before the last menstrual period, yielded null results, and further strengthened the accuracy of the approach we used to determine the last menstrual period. While an increasing number of studies have shown that benzodiazepines used during pregnancy do not appear to be associated with an elevated risk of adverse pregnancy outcomes, 27,33,34 concerns regarding teratogenicity and fetal developmental impairments persist. In our study, an increased risk of miscarriage associated with benzodiazepine use during early pregnancy was observed after accounting for measurable confounders, and the results were unlikely to be due to unmeasured confounding.…”
Section: Discussionmentioning
confidence: 99%
“…While an increasing number of studies have shown that benzodiazepines used during pregnancy do not appear to be associated with an elevated risk of adverse pregnancy outcomes, 27,33,34 concerns regarding teratogenicity and fetal developmental impairments persist. In our study, an increased risk of miscarriage associated with benzodiazepine use during early pregnancy was observed after accounting for measurable confounders, and the results were unlikely to be due to unmeasured confounding.…”
Section: Sensitivity Analysesmentioning
confidence: 99%